Explicating multitasking with computers: Gratifications and situations - Zhang, Weiyu; Zhang, Lingzi (Computers in Human Behavior, 2012)
Abstract: This study tries to test the theory of uses and gratifications and the theory of situated action as explanations of multitasking in computer-mediated communication. Based on the data collected from an online survey (N =234), we find that as hypothesized, different gratifications and situations are connected to different types of multitasking in different ways. In particular, multimedia and work-related multitasking are primarily driven by instrumental gratifications whereas affective gratifications contribute to multimedia and interaction type of multitasking. Situational factors have less powerful influence compared to gratifications. However, there are clear differences that discern types of computer multitasking along the situational dimension.